2022
DOI: 10.3389/fenvs.2022.1007959
|View full text |Cite
|
Sign up to set email alerts
|

Why do consumers buy recycled shoes? An amalgamation of the theory of reasoned action and the theory of planned behaviour

Abstract: The footwear industry’s transition to a circular economy is a essential for sustainable development. The emerging recycled shoe production may lead to sustainable consumption in the footwear industry. Consumers are now more cognizant of the negative effects of their shopping choices. We studied the factors influencing consumers’ intentions of buying recycled shoes. We applied the theory of reasoned action (TRA) and the theory of planned behaviour (TPB). As this is an emerging trend, there is a dearth of suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Shrum et al [78] observed that an individual's concern or interest in environmental issues increases their ecological awareness of climate change. Yadav et al [79] integrated the theory of rational and planned behaviour into the context of sustainable consumer behaviour. The results pertaining to ecological consciousness obtained in the present study are consistent with previous studies in which subjective experience and perceived behavioural control were integrated.…”
Section: Discussionmentioning
confidence: 99%
“…Shrum et al [78] observed that an individual's concern or interest in environmental issues increases their ecological awareness of climate change. Yadav et al [79] integrated the theory of rational and planned behaviour into the context of sustainable consumer behaviour. The results pertaining to ecological consciousness obtained in the present study are consistent with previous studies in which subjective experience and perceived behavioural control were integrated.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of CE, consumer behavior implicitly encompasses aspects of SC [50], and consumer intervention can be reflected in the basic concept of the 3Rs [6] and its variants [50]. In other words, the consumer has a sustainable behavior when repairing, extending the shelf life of the product even considering the implicit design limitations [70], how difficult it is to allocate time to repair, and how easy it is to purchase a new product online [71]; recycling, sending products to a treatment process so that their materials serve as raw material for new materials or products, contemplating the differences in product categories and the type of recycling of these [72]; rethinking/reusing, considering the financial and social benefits of renting or buying second-hand products [45,73,74]; refurbishing a product, understood as improving the functional performance of an item (e.g., laptop), to keep it updated [75]; or remanufacturing, which involves the producer restores the product preserving its original function and added value [76]. Ref.…”
Section: The "Symbiotic" Relationship Between Sustainable Consumption...mentioning
confidence: 99%
“…A concrete analysis of the interaction of the sustainable consumer with key aspects of CE is required. For example, it is not very useful to sell a product made from recycled materials if consumers are not willing to buy them [72]; therefore, it is necessary to scientifically investigate the factors that condition the success of such products, considering geographical, demographic, psychographic variables, among others. In another example, if they perceive remanufactured products as inferior or are unwilling to buy them for a profitable price [76], there would be no real incentive for companies to perform such an action of the circular ecosystem.…”
Section: Sustainable Consumption As a Requirement For Circular Economymentioning
confidence: 99%
“…Consumers currently have a strong interest in sustainable consumption (Hosta and Zabkar, 2021;Yadav et al, 2022). Manufacturers and retailers have responded to this trend by integrating sustainability initiatives, such as the development and launch of new products and brands with positive health, social and environmental attributes (Swaen et al, 2021).…”
Section: Research Modelmentioning
confidence: 99%